The Effect of Addition RAP as Quality Improved for Hot Paved Mixtures - Irfan Zhain; Ria A. A. Soemitro; Hitapriya Suprayitno (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Reclaimed Asphalt Pavement (RAP) is the residual waste of pavement that has been damaged or has reached the end of the pavement by using a Cold Milling Machine (CMM). The old aggregate undergoes gradation changes due to traffic loads and weather effects so the gradation is not following the ideal gradation plan. The addition of natural aggregates aims to improve the grading envelope to meet the upper and lower limits of the AC-BC layer requirements. This study aims to determine the optimal composition of the RAP material in terms of Marshall characteristics. The use of RAP material variations is 30%, 40%, and 50% of the total composition of the mixture. This study refers to the 2018 Bina Marga specifications and the Marshall method for laboratory testing. The research steps consisted of material extraction testing, aggregate and asphalt properties, sieve analysis tests for mixed grading envelopes, and Marshall tests.The results of this study are the characteristics of the mixture in terms of Marshall stability for the composition of RAP 30%, the stability value is 1433.3 Kg, RAP 40% is 1621.7 Kg, and RAP 50% is 1920.8 Kg. The greater the composition of the RAP, the greater the stability value, which shows the strong mixed nature of holding vehicle traffic loads